Cardiovascular associations of falls and syncope in the elderly - BHANGU, JASPREET SINGH (Trinity College Dublin. School of Medicine. CentreFor Medical Gerontology, 2017)
The principle aims of this doctoral investigation are to provide new insights into the relationship between cardiovascular disease (CVD) and falls in the elderly population in Ireland. The rapidly ageing global demographic has meant that there will be a significant increase in healthcare burden from chronic disease. Falls are currently the most common cause of injury and resulting morbidity in people over the age of 65 years. Risk factors for falls have been established, however there has been very little in the way of measures which have proven preventative. Initially I had performed a literature review aiming to discern cardiovascular disorders which were associated with falls in the elderly. This had allowed me to systematically evaluate what associations have already been reported in the literature and where inconsistency still exists. This demonstrated multiple reported associations of cardiovascular disorders with falls, unexplained falls and syncope in elderly people. I have focused on disorders which result in syncope but can present as a fall in elderly patients. For my second paper I have used the Irish longitudinal Study Ageing (TILDA) to calculate the prevalence of falls, unexplained falls and syncope in the community dwelling Irish population. Also using the TILDA database I have been able to formulate logistic regression models which can be used to calculate odds ratios for self-reported health conditions and the exposures above. This allowed me to explore some of the associations in more depth using an observational study design. My third paper looked a cohort of patients who had presented to the emergency department during the time that we were conducting the observational study. Using electronic data linked to their medical records number I was able to estimate what the prevalence of unexplained falls, explained falls and syncope was in the emergency department. Additionally I used pre-specified resource variables to give some insight into the differences in resource usage between these groups when they present to the emergency department. For my fourth paper I have looked in more depth at the exact causes of the overlap of syncope and falls in the elderly. To do this we designed a study which examined all patients over the age of 50 who had presented to an emergency department in an urban hospital (St. James?s Hospital Dublin) with two or more unexplained falls in the last year. We entered 70 of these patients into a clinical trial to examine in more detail for the presence of cardiac arrhythmia which may be the underlying cause of the fall or syncopal episode. Lastly I have explored one of the risk factors which have been identified in the fifth paper- namely depression and medications which may contribute to syncope. This was again done at a population level using the TILDA database in order to make associations and draw conclusions.
APPROVED
Keywords: Cardiovascular disease; Ageing